Students' perceptions of classroom assessment practices (CAPs) and its relationship among the six CAPs scales / Nadia Ibrahim, Zurina Khairuddin and Zulaikha Khairuddin - Ibrahim, Nadia; Khairuddin, Zurina; Khairuddin, Zulaikha (Universiti Teknologi MARA Shah Alam, 2018)
This study investigated the students' perceptions of Classroom Assessment Practices (CAPs) in Malaysian Higher Education Institutions (MHEIs). The objective of this study was to explore students' perceptions towards CAPs and investigate if there is any relationship among the students' perceptions towards the six scales of CAPs. There were 109 participants participating in this study and they were randomly chosen from first semester of diploma students in Malaysian Higher Education Institutions (MHEIs). This study employed quantitative research method utilising questionnaire survey, adopted and adapted from Fisher, Waldrip, & Dorman (2005). The data were analysed using Statistical Package for Social Sciences (SPSS) software. The findings of the study suggested that the students in MHEIs agreed the CAPs implemented were congruent with planned learning, authentic and transparent,a mean to consult the lecturers and classmates, appropriately matched with their level and capability and have helped them to develop and improve their soft skillsand there was a significant positive correlation among the six scales of CAPs. The recommendations and limitations of this study were also discussed.